Market Structure in Services and Market Access in Goods - Joseph Francois; Ian Wooton (Tinbergen Institute, 2004)
We examine interaction between trade in goods and market power in domestic trade and distribution, developing a model that highlights this interaction. Theory points to an expected linkage between service sector competition and goods trade, one supported by econometrics involving import patterns of 21 OECD countries vis-à-vis 86 trading partners. This points to significant linkages between effective market access conditions for goods and the structure of the service sector. Because of the implied interaction, ignoring the structure of the domestic service sector may lead to a substantial underestimation of the direct impact of tariffs on trade flows.
Keywords: F12; F13; F23; 330; market access; services trade; trade liberalization; competition policy; imperfect competition; GATS; Internationale Wirtschaft; Marktmacht; Dienstleistungshandel; Handelsliberalisierung; Wettbewerbspolitik